Comparative equality and diversity: main findings and research gaps. Issue 3 (1st August 2016) - Klarsfeld, Alain; Ng, Eddy S.W.; Booysen, Lize; Castro Christiansen, Liza; Kuvaas, Bård
Abstract : Purpose: – This is a special issue introduction on cross-cultural and comparative diversity management (DM). The purpose of this paper is to present five articles that explore and examine some of the complexities of equality and DM in various countries around the world. Design/methodology/approach: – In this introductory paper, the authors provide an overview and the current state of literature on comparative research on equality and diversity. The authors also gathered a list of indices that is helpful as secondary data for informing comparative and cross-national research in this domain. Findings: – To date, comparative work involving two or more countries is scarce with Canada/USA comparisons first appearing in the 1990s, followed by other groupings of countries a decade later. Existing comparative work has started to uncover the dialectics of voluntary and mandated action: both complement each other, although the order in which they appear vary from context to context. This work also acknowledges that there are varying degrees of intensity in the way that legislations may constrain employer action in encouraging a more diverse workforce, and that there is more than a binary choice between blind equality of rights (identity blind) and quota-based policies (affirmative action) available to decision makers. Originality/value: – The comparative nature of these papers allows the reader to compare and contrast the different approaches to the adoption and implementation of DM. The authors also draw attention to several areas in cross-cultural DM research that have been understudied and deserve attention.